2018
DOI: 10.1002/pc.25086
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of kaolinite/polyaniline nanocomposites and investigating their anticorrosive performance in chlorinated rubber/alkyd coatings

Abstract: Kaolinite/polyaniline nanocomposites (KPAns) were prepared by in situ chemical oxidative polymerization. The nanocomposites were synthesized with four different aniline to kaolinite weight percentage; 5, 10, 15, and 20% to produce KPAn5, KPAn10, KPAn15, and KPAn20, respectively. The structural, morphological and thermal properties of the nanocomposites were characterized using Fourier transform infrared, X‐ray diffraction, scanning electron microscope (SEM)–energy dispersive X‐ray analyzer, transmission electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…Table displays the comparisons of electrochemical parameters of the present work with the reported data. It can be concluded that the electrochemical performance of the EP-TMSPMA/clay nanocomposite was found to be superior to other reported nanocomposite coatings. …”
Section: Results and Discussionmentioning
confidence: 82%
“…Table displays the comparisons of electrochemical parameters of the present work with the reported data. It can be concluded that the electrochemical performance of the EP-TMSPMA/clay nanocomposite was found to be superior to other reported nanocomposite coatings. …”
Section: Results and Discussionmentioning
confidence: 82%
“…It's well known that chlorinated rubber has excellent corrosion resistance and water resistance. 40 During the early stages of coating immersion in the water environment, chlorinated rubber acted as a protective barrier, resulting in a slow Ag + release rate in the rst stage. The release behaviour at this stage was similar to that reported in the literature.…”
Section: Composite Coatings Characterization and Ag + Release Analysismentioning
confidence: 99%
“…Corrosion rate (CR) in millimeters per year (mm/y) was calculated from Faraday's law equation (2) [22,25,26] where K is a constant that defines the units of corrosion rate and equals to 3272 mm/y, EW is the equivalent weight in grams/equivalent, d is the density in g/cm3, A is sample area in cm2.…”
Section: Potentiodynamic Polarization Measurementsmentioning
confidence: 99%
“…The coating efficiency (η%) was calculated according to equation (3) [25,27] where Icorr and I o corr are the corrosion currents in the absence and the presence of the coating, respectively.…”
Section: Potentiodynamic Polarization Measurementsmentioning
confidence: 99%